2022
DOI: 10.1101/2022.08.21.504612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic anti-phage activity of bacterial defence systems

Abstract: Anti-phage defence systems in bacterial genomes have a vast intra- and inter-species diversity. Here we investigated whether combinations of defence systems are selected for or against due to the effects of anti-phage protection. Analysis of defence system co-occurrence in Escherichia coli genomes revealed that positive and negative co-occurrences are common, and surprisingly both can provide synergistic anti-phage activities. Furthermore, we did not find conserved patterns of defence system co-occurrence acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 112 publications
1
11
1
Order By: Relevance
“…1). Notably, each serovar appears to have a distinct profile of defence systems, suggesting selection of the most beneficial systems in specific environments or host interactions, as previously observed for distinct E. coli phylogroups 44 . For example, in serovars Typhi and Paratyphi A, the 3HP and Druantia type III systems are highly abundant.…”
Section: Anti-phage Defence Systems Are More Prevalent In Chromosomal...supporting
confidence: 53%
“…1). Notably, each serovar appears to have a distinct profile of defence systems, suggesting selection of the most beneficial systems in specific environments or host interactions, as previously observed for distinct E. coli phylogroups 44 . For example, in serovars Typhi and Paratyphi A, the 3HP and Druantia type III systems are highly abundant.…”
Section: Anti-phage Defence Systems Are More Prevalent In Chromosomal...supporting
confidence: 53%
“…Our findings demonstrate the significance of the individual defense systems in predicting the susceptibility of P. aeruginosa strains to phages. However, factors such as genetic context, interactions among defense systems (49,(51)(52)(53), the presence of unknown defense systems, and anti-defense mechanisms will affect the final outcome of phage infection. Further research is required to enhance the predictive accuracy of genomic analysis, which could prove beneficial for ecological and evolutionary studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this aggregation of defense systems within mobile elements provides fitness benefits to recipient bacteria living in a phage-rich environment [1]. It has also been suggested that synergism between defense systems may promote their co-localization within and co-transfer between genomes [22,46,47]. Genes involved in bacterial pathogenicity are frequently mobilized between bacteria on "pathogenicity islands", which constitute MGEs carrying clusters of pathogenicity genes [48].…”
Section: Plos Geneticsmentioning
confidence: 99%